2021
DOI: 10.4315/jfp-20-227
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylation System of Shewanella baltica Regulates Putrescine Production and Acid Resistance

Abstract: Shewanella baltica , as one of the dominant spoilers in seafoods where they encounter acidic environments during spoilage, can synthesize putrescine from ornithine and cause food spoilage as well as health problems. Here, the ornithine decarboxylation (ODC) pathway composed of ornithine decarboxylases SpeC and SpeF and an ornithine-putrescine transporter PotE were identified in S. baltica by database searches and further by molecular biology operations, and SpeC functioned as an auxiliary adjusting component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The fermentation results showed that blocking these two genes promoted the accumulation of L -ornithine; the L -ornithine titers of the NBO1 and NBO2 strains reached 1.97 g/L and 1.95 g/L, respectively. In addition, the speF gene, encoding L -ornithine decarboxylase ( Bao et al, 2021 ), was knocked out to block the catabolism of L -ornithine to putrescine in B. amyloliquefaciens NBO3 [with argF and argI genes deleted in B. amyloliquefaciens NB (Δ pgsBCA )], thereby obtaining the B. amyloliquefaciens strain NBO4. The L -ornithine titer of NBO4 was further increased to 3.51 g/L ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…The fermentation results showed that blocking these two genes promoted the accumulation of L -ornithine; the L -ornithine titers of the NBO1 and NBO2 strains reached 1.97 g/L and 1.95 g/L, respectively. In addition, the speF gene, encoding L -ornithine decarboxylase ( Bao et al, 2021 ), was knocked out to block the catabolism of L -ornithine to putrescine in B. amyloliquefaciens NBO3 [with argF and argI genes deleted in B. amyloliquefaciens NB (Δ pgsBCA )], thereby obtaining the B. amyloliquefaciens strain NBO4. The L -ornithine titer of NBO4 was further increased to 3.51 g/L ( Figure 2B ).…”
Section: Resultsmentioning
confidence: 99%
“…3,19 Pereira et al demonstrated that certain microorganisms, such as Citrobacter freundii and Lactobacillus collinoides, can modulate their intracellular pH by converting ornithine to putrescine. 20 This conversion is mediated by the ornithine-dependent acid-fast system, which involves the enzymes ODC (SpeF/ODC) and the antiporter PotE, 21 which decarboxylates under the action F I G U R E 7 Phylogenetic analysis: ornithine decarboxylase (ODC) and other pyridoxal-5′-phosphate (PLP)-dependent amino decarboxylases. Each protein sequence in the phylogenetic tree is accompanied by its corresponding NCBI database number and protein source.…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al. demonstrated that certain microorganisms, such as Citrobacter freundii and Lactobacillus collinoides , can modulate their intracellular pH by converting ornithine to putrescine 20 . This conversion is mediated by the ornithine‐dependent acid‐fast system, which involves the enzymes ODC (SpeF/ODC) and the antiporter PotE, 21 which decarboxylates under the action of ODC, consuming protons and generating putrescine and gaseous ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…BAs are primarily created by bacteria using substrate-specific decarboxylase enzymes to decarboxylate the relevant amino acids. Because they are frequently active at acidic pH levels, these enzymes may assist in retaining pH homeostasis or shorten the development time by detoxifying the extracellular medium [ 6 ]. Free amino acids, the existence of decarboxylase-positive microbes and favorable conditions for bacterial development are all factors that the procedure of fermentation of fish may give [ 7 ].…”
Section: Introductionmentioning
confidence: 99%